2006
DOI: 10.1111/j.1523-1739.2006.00412.x
|View full text |Cite
|
Sign up to set email alerts
|

Remote Forest Refugia for Fijian Wildlife

Abstract: On Pacific islands non-native rats and mongooses threaten many native species. In Fiji we compared visitation rates of rats and mongooses at bait stations and measured biomass of leaf-litter invertebrates to assess the relative predation pressure from these species in forest areas at different distances from the forest edge. Forest areas over 5 km from the forest edge had significantly fewer baits encountered by rats or mongooses than did natural forest areas nearer agricultural and urban habitats. Remote fore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 11 publications
(10 reference statements)
0
12
2
Order By: Relevance
“…Both artificial nests and waxtags experienced significantly higher rat predation rates in sites near to mixed taro and banana plantations than either edge sites away from plantations or interior forest sites. Unlike Olson et al (2006), we found no significant difference between edge habitats (away from plantations) and interior forest sites (>1 km from the edge). We hypothesize that as the proportion of forest edge near plantations increases, which is expected with continual plantation development, a larger proportion of forest bird populations will experience nest predation from black rats.…”
Section: Discussioncontrasting
confidence: 87%
See 3 more Smart Citations
“…Both artificial nests and waxtags experienced significantly higher rat predation rates in sites near to mixed taro and banana plantations than either edge sites away from plantations or interior forest sites. Unlike Olson et al (2006), we found no significant difference between edge habitats (away from plantations) and interior forest sites (>1 km from the edge). We hypothesize that as the proportion of forest edge near plantations increases, which is expected with continual plantation development, a larger proportion of forest bird populations will experience nest predation from black rats.…”
Section: Discussioncontrasting
confidence: 87%
“…They found significantly lower visitation rates at forest interior sites (>1 km from the edge) than at sites closer to the forest edge. Unlike Olson et al (2006), we found no significant difference between edge habitats (away from plantations) and interior forest sites (>1 km from the edge). Our study suggests that the bird populations breeding in these forest types may be experiencing nest predation rates similar to those breeding in edge habitat away from plantations.…”
Section: Discussioncontrasting
confidence: 87%
See 2 more Smart Citations
“…There are several other important and continuing threats to ecosystems in Oceania, including invasive species, which impact native biodiversity in all ecosystems (Lonsdale 1994;Craig et al 2000;Olson et al 2006). For example, there are many introduced species in New Zealand; at least 30 mammals, 34 birds, 2000 invertebrates, and 2200 plants Norton 2009).…”
Section: Altered Rainfall Patterns and Increased Fire Frequencymentioning
confidence: 99%